2019
DOI: 10.1002/wer.1161
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the use of mainstream iron addition for phosphorous control on H2S content of biogas from anaerobic digestion of sludges

Abstract: A material flux analysis on sulfur (S), phosphorus (P), aluminum (Al), and iron (Fe) was conducted for two WWTPs (Galt and Kitchener) to evaluate the potential of coagulants that are employed for phosphorus control to reduce hydrogen sulfide (H2S) emissions in the biogas from anaerobic digestion. It was found that while the Galt WWTP receives higher concentrations of S in the raw wastewater than the Kitchener WWTP, this had only a modest impact on the speciation of S entering anaerobic digestion. At both plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…For wastewater treatment plants, operators have expressed concerns that the addition of waterworks sludge could affect the drainage properties of the digestate. The opposite effect is indicated by literature data, finding that the drainage of biosolids after the addition of waterworks sludge is improved [13,18].…”
Section: Observed Operational Conditions When Mixing Waterwork Sludge With Substrate and Feeding The MIX Into Digestersmentioning
confidence: 82%
See 2 more Smart Citations
“…For wastewater treatment plants, operators have expressed concerns that the addition of waterworks sludge could affect the drainage properties of the digestate. The opposite effect is indicated by literature data, finding that the drainage of biosolids after the addition of waterworks sludge is improved [13,18].…”
Section: Observed Operational Conditions When Mixing Waterwork Sludge With Substrate and Feeding The MIX Into Digestersmentioning
confidence: 82%
“…It has been reported that around 2-4% of influent S enters the digesters, which could be removed sufficiently by a dosage of 1.1 mg/L of Fe into the raw wastewater. A higher dry matter content was also observed in the dewatered cake as an additional secondary benefit when changing from alum dosage to iron dosage for phosphorous removal [13]. A drop in hydrogen sulfide emission from full-scale ADs at a large-scale municipal wastewater treatment plant could be achieved when dosing ferric chloride.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Industrial filters allow for the precise separation of the sulphur compounds contained in the biogas, but this is associated with considerable operating costs [78]. As far as the protection of electricity generators or CHP plants is concerned, the techniques for cleaning the biogas from H2S have a significant impact on the cost of the plants, and abandoning them or replacing them with biological filters leads to a drastic reduction in the lifetime of generators and anaerobic reactor systems [79]. In desulphurisation technology based on the use of a steel valve bed, it is possible to easily obtain a substrate for the production of this adsorber and also to easily modify existing solutions [80].…”
Section: Biogenic Compounds Removalmentioning
confidence: 99%
“…sewer system and other downstream treatment units such as AS system or AD in WWTP. Direct dosing of Fe-salt in sewers (Ganigue et al, 2011b;Gutierrez et al, 2010;Zhang et al, 2009b;Zhang et al, 2010) and AD (Akgul et al, 2017;Park and Novak, 2013;Parker et al, 2019) for controlling sulfides or chemical P precipitation with Fe-salt in AS system (de Haas et al, 2000;de Haas et al, 2001;Gutierrez et al, 2010), have been established as the proven practices. Such a strategy of direct Fe-salt dosing has been reported to improve settleability (Oikonomidis et al, 2010) and dewaterability (Wei et al, 2018) of activated sludge including the dewaterability of digestate (Novak and Park, 2010;Akgul et al, 2017).…”
Section: Settleability and Dewaterability Of Sludgesmentioning
confidence: 99%